Towards Flawless Designs: Recent Progresses in Non-Orthogonal Multiple Access Technology - Dai, Gaoyuan; Huang, Ronglan; Yuan, Jing; Hu, Zeng; Chen, Longru; Lu, Jianxian; Fan, Tianrui; Wan, Dehuan; Wen, Miaowen; Hou, Tianwei; Ji, Fei (Electronics, 2023)
High effectiveness and high reliability are two fundamental concerns in data transmission. Non-orthogonal multiple-access (NOMA) technology presents a promising solution for high-speed data transmission, which has long been pursued by academia and industry. However, there is still a significant road ahead for it to effectively support a wide range of applications. This paper provides a comprehensive study, comparison, and classification of the current advanced NOMA schemes from the perspectives of single-carrier (SC) systems, multicarrier (MC) systems, reconfigurable-intelligent-surface (RIS)-assisted systems, and deep-learning (DL)-assisted systems. Specifically, system implementation issues such as the transition from SC-NOMA to MC-NOMA, the relaxation of distinct channel gains, the consideration of imperfect channel knowledge, and the mitigation of error propagation/intra-group interference are involved. To begin with, we present an overview of the state-of-the-art developments related to the advanced design of SC-NOMA. Subsequently, a generalized MC-NOMA framework that provides the diversity–multiplexing gain by enhancing users’ signal-to-interference-plus-noise ratio (SINR) is proposed for better system performance. Moreover, we delve into discussions on RIS-assisted NOMA systems, where the receiver’s SINR can be enhanced by intelligently reconfiguring the reflected signal propagations. Finally, we analyze designs that combine NOMA/RIS-NOMA with DL to achieve highly efficient data transmission. We also identify key trends and future directions in deep-learning-based NOMA frameworks, providing valuable insights for researchers in this field.
CRIS-Team Scopus Importer:2024-12-16
Keywords: deep learning (DL); multicarrier framework; multiplexing and diversity; non-orthogonal multiple-access (NOMA); reconfigurable intelligent surface (RIS); single-carrier paradigm